Gene Expression in Embryos From Norwegian Red Bulls With High or Low Non Return Rate: An RNA-Seq Study of in vivo-Produced Single Embryos - Diaz-Lundahl, Sofia; Sundaram, Arvind Y.M.; Gillund, Per; Gilfillan, Gregor Duncan; Olsaker, Ingrid; Krogenæs, Anette (Frontiers in Genetics, 2022)
During the last decade, paternal effects on embryo development have been found to have greater importance than previously believed. In domestic cattle, embryo mortality is an issue of concern, causing huge economical losses for the dairy cattle industry. In attempts to reveal the paternal influence on embryo death, recent approaches have used transcriptome profiling of the embryo to find genes and pathways affected by different phenotypes in the bull. For practical and economic reasons, most studies have used in vitro produced embryos. The aim of the present study was to investigate the differences in the global transcriptome of in vivo produced embryos, derived from sires with either high or low field fertility measured as the non-return rate on day 56 after first AI of the inseminated cows. Superovulated heifers (n = 14) in the age span of 12-15 months were artificially inseminated with semen from either high fertility (n = 6) or low fertility (n = 6) bulls. On day seven after insemination, embryos were retrieved through uterine flushing. Embryos with first grade quality and IETS stage 5 (early blastocyst), 6 (blastocyst) or 7 (expanded blastocyst) were selected for further processing. In total, RNA extracted from 24 embryos was sequenced using Illumina sequencing, followed by differential expression analysis and gene set enrichment analysis. We found 62 genes differentially expressed between the two groups (adj.p-value<0.05), of which several genes and their linked pathways could explain the different developmental capacity. Transcripts highly expressed in the embryos from low fertility bulls were related to sterol metabolism and terpenoid backbone synthesis, while transcripts highly expressed in the high fertility embryos were linked to anti-apoptosis and regulation of cytokine signaling. The leukocyte transendothelial migration and insulin signaling pathways were associated with enrichments in both groups. We also found some highly expressed transcripts in both groups which can be considered as new candidates in the regulation of embryo development. The present study is an important step in defining the paternal influence in embryonic development. Our results suggest that the sire’s genetic contribution affects several important processes linked to pre-and peri implantation regulation in the developing embryo.